Analisis Tingkat Kesiapan Manajemen Layanan IT Berdasarkan Service Design Framework Itil V4 - Wafrina, Nadiatu; Yusuf, Ahmad; Ananto, Prasasti Karunia Farista (Universitas Multi Data Palembang, 2024)
The implementation of IT service management requires a framework to help companies interpret the form and function of IT implementation. The framework used as a guide for implementing IT service management is ITIL. ITIL V4 contains guidance that focuses on company management and customer satisfaction. The practice in ITIL that is related to the benefits received by the business is service design. FunBahasa as an IT service platform requires standardization of IT services with ITIL V4 practice service design which can help design IT services that are in line with business objectives. A readiness level analysis was carried out to determine the existing conditions at FunBahasa using maturity level indicators in the 4 dimensions of ITIL V4 with the results that The overall level is at level 2, this explains that the process or function has been implemented but has not yet been implemented. There are 3 recommendations for improving services in the organization and people dimension and the information and technology dimension and also 2 recommendations in the partners and suppliers dimension and the value stream and dimensions. processes